Organization of thoracic surgical services during the COVID pandemic. Issue 1 (February 2021) - Leow, Lowell; Ramanathan, Kollengode; Kofidis, Theo; Tam, John Kit Chung; Mithiran, Harish
Abstract: Introduction: COVID-19 presented an unprecedented challenge for healthcare workers and systems around the world. Healthcare systems have adapted differently in terms of pandemic planning of regular services, adopting infection control measures and prioritising essential hospital services in the context of a burgeoning COVID-19 patient load and inevitable surge. Methods: We performed a review on current evidence and share our practices at a teaching hospital in Singapore. Results: We outline principles and make recommendations for continuity of delivering essential thoracic surgical services during this current outbreak. Conclusions: The maintenance and provision of thoracic surgery services in this context requires good preplanning and vigilance to infection control measures across all levels. Highlights: Systematic review on current evidence for thoracic surgery during a pandemic. Provision of services involves preplanning, infection control and prioritization. Research, resident training and ethical considerations are also important.